MOTIF BATIK SRI TANJUNG KARYA HADI SUMARNO INDRAGIRI HILIR RIAU DALAM PERSPEKTIF ESTETIKA - Yatim, Rusman (Jurnal Ilmu Budaya, 2018)
The research entitled Batik Motives Sri Tanjung by Hadi Sumarno from Indragiri Hilir Riau in Aesthetic Perspective, it analyzes the exixtence, development, meaning and aesthetical creation of the motives. The main purpose of this reseach is to find the philosophical meaning of the motives creation and will be described deeply, and widely based on the aesthetic theory perspective.